Modulation of gastric acid secretion by cannabinoids in rats. Issue 3 (1st November 2018) - Salama, Rania A. A.; Abdelsalam, Rania M.; Abdel‐Salam, O. M. E.; khattab, Mahmoud M.; Salem, Neveen A.; El‐Khyat, Zakaria A.; Morsy, Fatma A.; Eldenshary, Ezz‐El Din S.
Abstract: The current study aimed to evaluate the role of cannabinoid receptors in the regulation of gastric acid secretion and oxidative stress in gastric mucosa. To fulfill this aim, gastric acid secretion stimulated with histamine (5 mg/kg, subcutaneous [SC]), 2‐deoxy‐d ‐glucose (D‐G) (200 mg/kg, intravenous) or ‐carbachol (4 μg/kg, SC) in the 4‐hour pylorus‐ligated rats. The CB1R agonist ( N ‐arachidonoyl dopamine, 1 mg/kg, SC) inhibited gastric acid secretion stimulated by D‐G and carbachol but not in histamine, reduced pepsin content, and increased mucin secretion. Furthermore, it decreased malondialdehyde (MDA) and nitric oxide (NO) contents with an increase in glutathione (GSH) and paraoxonase 1 (PON‐1). Meanwhile, CB2R antagonist (AM630, 1 mg/kg, SC) inhibited gastric acid secretion stimulated by D‐G and reduced MDA and NO contents with an increase in GSH and PON‐1. Meanwhile, CB1R antagonist rimonabant or CB2R agonist GW 405833 had no effect on stimulated gastric acid secretion. Therefore, both CB1R agonist and CB2R antagonist may exert antisecretory and antioxidant potential in the stomach.